Role of Divestment in Realizing the Welfare of Indonesian - Suwarsit, Suwarsit (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2023)
Welfare state is a country that participates in the economic interests of its people. Divestment is the sale of business carried out by a company and is the opposite of investment. Given the definitions, this study aims to find out if divestment can create an Indonesian welfare state. The results of the study show that in realizing the Indonesian welfare state, divestment should be carried out by foreign companies by selling their shares to the Indonesian side through the sovereignty owned by the Indonesian State in the mineral and coal mining sector. Sovereignty owned by the Indonesian state plays an important role for the Indonesian state to oblige the divestment of foreign companies. Without the sovereignty of the Indonesian state, the divestment of foreign companies in Indonesian is unlikely to occur.